Experimental subjective and objective analysis of speech intelligibility and acoustic comfort conditions in an unchanged XVII century Italian church. (30th March 2023) - Domenighini, P.; Belloni, E.; Buratti, C.
Highlights: Appropriateness of acoustic standards in churches from the listener's perception. Multidisciplinary approach: architectural acoustics, phonetics and history of worship. A study conducted in an original building never renovated. Study on the phonetic and spectral components of the original sacred text. Abstract: Listening conditions are a usual topic for places of worship. Santa Maria della Consolazione in Todi is one of the few examples of worship spaces in quasi-unchanged condition since its construction in 1607, and it offers the opportunity to study the acoustics that existed during the Counter-Reformation. Some of the most famous Italian architects worked on this project, and an apparent lack of consideration for acoustic comfort within the enclosed space was the reason for investigating its T 30, C 50, and STI parameters according to ISO 3382:1-2009 and IEC 60268-16. The measurements showed uncomfortable speech listening conditions ( T 30 = 9 s at 500 Hz, C 50 = -8.6 dB at mid frequencies, average STI = 0.34) and were compared with other acoustic comfort conditions studies from the literature. To ensure the usefulness of using these standards, the study was contextualized with the original form of speech from the Tridentine Missal, which was chosen for its organisation and rigour. The most significant phrase that has to be heard from the assembly was selected, and listening tests were performed in order to assess acoustic comfort and to match the results with the analysis output following the standards. Despite the bad results of the measurements according to the Standards, the listening tests results showed adequate acoustic behaviour due to the contextualization of the rite inside the church. Furthermore, potential advantages of the original Latin text over a modern Italian translation were spectrally and phonetically demonstrated.